The Influence of Financial Literacy, Financial Technology, and Financial Behavior on the Financial Performance of SMEs in Malahayu Village - Alamsyah, Rizki; Sijabat, Rauly; Nastiti, Prianka Ratri (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, making a significant contribution to national GDP and providing resilience during the economic crisis. However, MSMEs often face challenges in terms of capabilities, human resources and marketing. This research aims to examine the influence of financial literacy, financial technology and financial behavior on the financial performance of MSMEs in Malahayu Village. Using a quantitative approach, data was collected from 100 MSMEs through purposive sampling and analyzed using multiple linear regression. The research results show that financial literacy, financial technology and financial behavior have a significant and influential effect on the financial performance of MSMEs. In the F test, financial literacy, financial technology and financial behavior simultaneously and significantly influence the financial performance of MSMEs in Malahayu Village. This study contributes to understanding the relationship between financial knowledge, technology and behavior in improving tourism and MSME performance.